2015
DOI: 10.18632/oncotarget.4290
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non-coding RNA HOTAIR inhibits malignant biological behaviors of human glioma cells via modulation of miR-326

Abstract: Glioma is the most common and aggressive primary adult brain tumor. Long non-coding RNAs (lncRNAs) have important roles in a variety of biological properties of cancers. Here, we elucidated the function and the possible molecular mechanisms of lncRNA HOTAIR in human glioma U87 and U251 cell lines. Quantitative RT-PCR demonstrated that HOTAIR expression was up-regulated in glioma tissues and cell lines. Knockdown of HOTAIR exerted tumor-suppressive function in glioma cells. Further, HOTAIR was confirmed to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
116
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 48 publications
3
116
1
Order By: Relevance
“…The pathways analysis results showed that there were four pathways related with cancer. In addition, Ke et al also found that the miR-326 was overexpressed after knockdown lncRNA HOTAIR in glioma cells, which reduced FGF1 expression by activating the PI3K/AKT pathway (55). Therefore, our results suggested that these key lncRNAs may play an important role in the progression and development of GC and the cancer genes related pathways.…”
Section: Discussionsupporting
confidence: 64%
“…The pathways analysis results showed that there were four pathways related with cancer. In addition, Ke et al also found that the miR-326 was overexpressed after knockdown lncRNA HOTAIR in glioma cells, which reduced FGF1 expression by activating the PI3K/AKT pathway (55). Therefore, our results suggested that these key lncRNAs may play an important role in the progression and development of GC and the cancer genes related pathways.…”
Section: Discussionsupporting
confidence: 64%
“…Recent evidence indicates that lncRNAs also play important roles in glioma pathogenesis . One of the notable lncRNAs, HOTAIR, plays an important role in regulating glioma cell cycle and progression by interacting with the PRC2 complex in the nucleus or interacting microRNAs in the cytoplasm . HOTAIR is transcribed in an antisense manner with respect to the canonical HOXC genes.…”
Section: Discussionmentioning
confidence: 99%
“…(6,7) With regard to RNA interactions between lncRNAs and miRNA in cancers, Hox transcript antisense intergenic RNA (HOTAIR), an lncRNA, has an oncogenic role in tumor formation by upregulating fibroblast growth factor 1 by sponging miR-326, which activates the PI3K/AKT and MEK1/2 pathways. (8) We also recently found that Notch1 activation in glioma cells specifically induced the expression of lncRNA for taurine upregulated gene 1 (TUG1), which coordinately promoted self-renewal by sponging miR-145. (9) Thus, accumulating studies of cancer-associated lncRNAs have reported their roles in the multiple pathological steps of tumorigenesis, including cell proliferation, cellular signaling, angiogenesis, and metastasis, which may provide a strong rationale for the targeting of lncRNAs as a specific and potent therapeutic approach to eliminate cancer cells.…”
mentioning
confidence: 95%
“…With regard to RNA interactions between lncRNAs and miRNA in cancers, Hox transcript antisense intergenic RNA (HOTAIR), an lncRNA, has an oncogenic role in tumor formation by upregulating fibroblast growth factor 1 by sponging miR‐326, which activates the PI3K/AKT and MEK1/2 pathways . We also recently found that Notch1 activation in glioma cells specifically induced the expression of lncRNA for taurine upregulated gene 1 (TUG1), which coordinately promoted self‐renewal by sponging miR‐145 …”
mentioning
confidence: 99%